Effect Of Portfolio Investment Optimization Risk-Based And Efficiency Investment On Investment Decision - Syahyono, S. (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2018)
During the current pandemic, the number of investors in Indonesia is increasing rapidly. It is an exciting thing how novice investors make decisions and face risks. On investment to minimize risk can be done with an investment portfolio. This study tries to offer investment efficiency factors and risk-based investment portfolio optimization so that investors in making investment decisions will feel satisfied and can meet their investment goals. The method used is descriptive quantitative. The sampling technique used the purposive sampling technique.The study results indicate that risk-based investment optimization and investment efficiency have a positive influence on investment decisions. It can ensure that accuracy in optimizing investment portfolios and increasing investment efficiency by investors can increase the efficiency of Investment Experience in investing.